2018
DOI: 10.3389/fmed.2018.00325
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Accuracy of Different Soluble fms-Like Tyrosine Kinase 1 and Placental Growth Factor Cut-Off Values in the Assessment of Preterm and Term Preeclampsia: A Gestational Age Matched Case-Control Study

Abstract: Introduction: The objective was to investigate the diagnostic accuracy of different thresholds of the soluble vascular endothelial growth factor receptor-1 (sFlt-1) and the placental growth factor (PlGF) in preterm (≤37 weeks) and term (>37 weeks) preeclampsia (PE).Materials and Methods: A nested case-control study was performed from a high-risk Swiss cohort. Only blood samples on the day of PE diagnosis were included. The primary outcome was to verify the diagnosis using the recently proposed cut-off values f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…For suspected pre-eclampsia, ISSHP recommends evaluation of angiogenic imbalance as a marker of uteroplacental dysfunction, whereas normal angiogenic balance would strengthen a diagnosis of gestational hypertension 2 . NICE guidelines and meta-analyses support the measurement of PGF alone or in combination with sFLT1 to rule out suspected pre-eclampsia within the 14 days following measurement 26,42,[228][229][230][231][232][233][234] . A stepped-wedge cluster trial demonstrated that measurement of PGF in women with suspected pre-eclampsia reduces the time to clinical confirmation and may reduce the incidence of adverse maternal outcomes 235 .…”
Section: Diagnosismentioning
confidence: 99%
“…For suspected pre-eclampsia, ISSHP recommends evaluation of angiogenic imbalance as a marker of uteroplacental dysfunction, whereas normal angiogenic balance would strengthen a diagnosis of gestational hypertension 2 . NICE guidelines and meta-analyses support the measurement of PGF alone or in combination with sFLT1 to rule out suspected pre-eclampsia within the 14 days following measurement 26,42,[228][229][230][231][232][233][234] . A stepped-wedge cluster trial demonstrated that measurement of PGF in women with suspected pre-eclampsia reduces the time to clinical confirmation and may reduce the incidence of adverse maternal outcomes 235 .…”
Section: Diagnosismentioning
confidence: 99%
“…We present a prospective, observational study which was conducted at the University Hospitals in Basel and Geneva, Switzerland [19]. The Competent Ethics Committee of Northwestern Switzerland and Geneva (IRB approval numbers EKNZ PB_2016_02490 and GE 14-216) approved the study protocol, and written informed consent was obtained from all participants.…”
Section: Study Design and Patientsmentioning
confidence: 99%
“…In normal pregnancies, the level of sFLT-1 starts to rise after 30-32 weeks of gestation and PlGF level starts to decrease after 30 weeks of gestation. Actually cellular stress in the syncytiotrophoblast, which occurs during the last 8-10 weeks of a pregnancy leads to biochemical changes in levels of sFlt-1 and PlGF in normal pregnancies [10]. Circulating levels of sFlt-1 and PlGF alter in PE patients.…”
Section: Introductionmentioning
confidence: 99%